2019
DOI: 10.1159/000497077
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal Tumor: A Silent Trespasser – Role of Image-Guided Fine-Needle Aspiration Cytology with Histopathological Correlation in Early Diagnosis

Abstract: Objective: Retroperitoneal lesions present a great diagnostic challenge. Here we analyze the spectrum of retroperitoneal lesions and the utility of cytohistopathological correlation in early diagnosis. Study Design: This 7-year study was undertaken in 338 patients with a retroperitoneal mass (kidney/adrenal/ pancreas/retroperitoneal lymph node, or soft tissue origin). In a prospective analysis, 81 patients underwent image-guided fine-needle aspiration cytology (FNAC) and 70 of the 81 underwent Tru-cut biopsy/h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Das et al reported an overall diagnostic accuracy rate for image-guided FNAC of 94.12%, though 28 inadequate specimens encountered in 338 cases and 37 cases needed repeat aspirations. 2 Perirenal fat mass in our patient was low (17 mm), thus it was considered that an adequate sample might not be fully obtained with a fine needle biopsy procedure and the patient requested a more reliable method of diagnosis. As a result, retroperitoneoscopic tumor resection was chosen, which led to the final diagnosis of prostate cancer.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Das et al reported an overall diagnostic accuracy rate for image-guided FNAC of 94.12%, though 28 inadequate specimens encountered in 338 cases and 37 cases needed repeat aspirations. 2 Perirenal fat mass in our patient was low (17 mm), thus it was considered that an adequate sample might not be fully obtained with a fine needle biopsy procedure and the patient requested a more reliable method of diagnosis. As a result, retroperitoneoscopic tumor resection was chosen, which led to the final diagnosis of prostate cancer.…”
Section: Discussionmentioning
confidence: 80%
“…Prostate cancer metastasis is most often found in bone, followed by lymph node, liver, and lung tissues. 2 However, to the best of our knowledge, there have been no reports of prostate cancer metastasis to perirenal fat tissue and present the first known case here.…”
Section: Introductionmentioning
confidence: 75%
“…Asim et al (9) reported that the sensitivity and speci city of FNAB for the diagnosis of malignant small round cell tumors (SRCT) were 97% and 100%, respectively. Similarly, Das et al (10) indicated that the sensitivity and speci city of FNAB for asymptomatic retroperitoneal masses were 98.02% and 72.22%, respectively. Furthermore, Koshy et al (11) pointed out that FNAB can identify pNT well.…”
Section: Discussionmentioning
confidence: 91%
“…The effectiveness of image‐guided FNAC has also been reported. The overall sensitivity, specificity and diagnostic accuracy of image‐guided FNAC was 98.02%, 72.22% and 94.12%, respectively 33 . However, the results also included epithelial tumors.…”
Section: Benign Rptsmentioning
confidence: 93%
“…The overall sensitivity, specificity and diagnostic accuracy of image-guided FNAC was 98.02%, 72.22% and 94.12%, respectively. 33 However, the results also included epithelial tumors. Needle biopsy over FNAC is recommended in European Society for Medical Oncology-European Network Reference for Rare Adult Solid Cancers Clinical Practice Guidelines and National Comprehensive Cancer Network Clinical Practice Guidelines.…”
Section: Validation Of Needle Biopsymentioning
confidence: 99%